A High-Density Genetic Linkage Map of SLAFs and QTL Analysis of Grain Size and Weight in Barley (Hordeum vulgare L.) - Fang, Yunxia; Zhang, Xiaoqin; Zhang, Xian; Tong, Tao; Zhang, Ziling; Wu, Gengwei; Hou, Linlin; Zheng, Junjun; Niu, Chunyu; Li, Jia; Wang, Wenjia; Wang, Hua; et al. (Frontiers in Plant Science, 2020)
Grain size is an important agronomic trait determines yield in barley, and a high-density genetic map is helpful to accurately detect quantitative trait loci (QTLs) related to grain traits. Using SLAF-seq technology, a high-density genetic map was constructed with a population of 134 recombinant inbred lines (RILs) deriving from a cross between Golden Promise (GP) and H602, which contained 12,635 SLAFs with 26,693 SNPs, and spanned 896.74 cM with an average interval of 0.07 cM on 7 chromosomes. Based on the map, a total of 16 QTLs for grain length, grain width and thousand-grain weight were detected on 1H, 2H, 4H, 5H and 6H. Among them, a major QTL locus qGL1, accounting for the max phenotypic variance of 16.7% was located on 1H, which is a new unreported QTL affecting grain length. In addition, the other two QTLs, qGL5 and qTGW5, accounting for the max phenotypic variances of 20.7% and 21.1% respectively, were identified in the same region, and sequencing results showed they are identical to HvDep1 gene. These results indicate that it is a feasible approach to construct a high-quality genetic map for QTL mapping by using SLAF markers, and the detected major QTLs qGL1, qGL5 and qTGW5 are useful for marker- assisted selection (MAS) of grain size in barley breeding.